2021
DOI: 10.17344/acsi.2021.6823
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity of Insecticide Thiamethoxam to Crayfish (Astacus leptodactylus): Alterations in Oxidative Stress Markers, ATPases and Cholinesterase

Abstract: Thiamethoxam (Thmx) is a globally used neonicotinoid pesticide contaminated in freshwater ecosystems with residues detected in fishery products. Astacus leptodactylus is a popular freshwater crustacean that is cultivated and exported in many countries. In this study, we investigated the acute toxic effects of Thmx on A. leptodactylus using various biomarkers (acetylcholinesterase, carboxylesterase, glutathione S-transferase, glutathione, superoxide dismutase, glutathione peroxidase, glutathione reductase, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…In addition to maintaining ionic regulation, they also provide the energy required for the transport of metabolites (Oluah et al, 2020;Temiz et al, 2018). In cray sh (Astacus leptodactylus) tissues, sublethal doses of TMX were reported to inhibit enzyme activities responsible for ion regulation (Na + /K + -ATPase, Ca 2+ ATPase) in a dose-dependent manner at 96 hours of exposure (Uçkun et al, 2021).In present study, Na + /K + -ATPase and Ca 2+ ATPase enzymes, which are renal ionoregulation enzyme parameters, showed a signi cant dose-dependent decrease in TMX exposure for 7 days (Fig. 5.).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to maintaining ionic regulation, they also provide the energy required for the transport of metabolites (Oluah et al, 2020;Temiz et al, 2018). In cray sh (Astacus leptodactylus) tissues, sublethal doses of TMX were reported to inhibit enzyme activities responsible for ion regulation (Na + /K + -ATPase, Ca 2+ ATPase) in a dose-dependent manner at 96 hours of exposure (Uçkun et al, 2021).In present study, Na + /K + -ATPase and Ca 2+ ATPase enzymes, which are renal ionoregulation enzyme parameters, showed a signi cant dose-dependent decrease in TMX exposure for 7 days (Fig. 5.).…”
Section: Discussionmentioning
confidence: 99%
“…al., 2018; Sera ni et al, 2019; Tian et al, 2018;Uçkun et al, 2021). According to recent studies, pesticides cause reversible or irreversible inactivation of AChE enzyme activity depending on the toxic effect of the compounds and as a result, cholinergic intoxication has been determined toxic effect of the compounds and as a result, cholinergic intoxication has been determined(Biancardi et al, 2022;Moss, 2020;Umar & Aisami, 2020) …”
mentioning
confidence: 99%
“…Acute toxic effects occur within a few minutes to several hours after poisoning by pesticides [77,[96][97][98]. Poisoning impacts peripheral muscarinic and nicotinic receptors, as well as the central nervous system [99][100][101][102][103]. Some manifestations of a cholinergic crisis include nausea, vomiting, diarrhea, abdominal cramp, urinary incontinence, miosis, salivation, lacrimation, bronchorrhea, bradycardia, hypotension, fasciculation, muscle paralysis, dizziness, confusion, seizures, coma, and respiratory failure [8,100,102,[104][105][106].…”
Section: Acute Toxic Effectsmentioning
confidence: 99%
“…The results of the study indicated that acute exposure to CPF for a short duration may induce dysregulation of the neurosecretory activity of PNSCs, altered biochemical activity of brain, and reduced locomotory/swimming performance in fishes. Uçkun et al [100] investigated the acute toxic effects of Thmx on A. leptodactylus using various biomarkers (acetylcholinesterase, carboxylesterase, glutathione S-transferase, glutathione, superoxide dismutase, glutathione peroxidase, glutathione reductase, and adenosinetriphosphatases). The 96 h LC 50 value of Thmx was 8.95 mg/L as active ingredient.…”
Section: Acute Toxic Effectsmentioning
confidence: 99%
“…With the development of IRCFS, there has been an increasing focus on studies about the acute toxicities of insecticides to non-target crayfish ( Biever et al., 2003 ; Barbee and Stout, 2009 ; Mamun et al., 2009 ; Barbee et al., 2010 ; Yu et al., 2017 ; Zhu et al., 2022 ; Liao et al, 2023 ; Uçkun et al., 2021 ; Huang et al., 2022 ; Sun et al., 2022 ). Thiamethoxam (THI) and chlorantraniliprole (CHI) are two common insecticides that are used in paddy fields and have been widely registered as single-agent products ( Mason et al., 2000 ; Hilton et al., 2016 ; Wei et al., 2019 ; Uçkun et al., 2021 ). In recent years, the blends of THI and CHI have become popular in IRCFS.…”
Section: Introductionmentioning
confidence: 99%